Transport accessibility and mobility: a forecast of changes in the face of planned development of the network of expressways and motorways in Poland - Kowalski, Michał; Wiśniewski, Szymon (European Spatial Research and Policy, 2019)
The article presents a forecast of changes in the level of transport accessibility and mobility in Poland as a result of the anticipated development of the network of expressways and motorways. The progress which has been made in this respect in the last few years in Poland is unquestionable and unrepeatable by any other European country. Will the subsequent investment plans concerning the road network of the highest parameters offer equally impressive results as far as the increase in Poland’s territorial cohesion is concerned? The aim of this article is to establish in what way the planned infrastructure investments will affect the changes in transport accessibility and mobility as well as whether they will result in the changes in traffic flows directed to Warsaw and other regional centres. To achieve this, an analysis of the present and target state of the road network in Poland was conducted from the perspective of changes in accessibility, anticipated traffic flows, and mobility. For this purpose the authors used the analyses of isochrone and accumulative accessibility in ArcMap environment and research into traffic flows and their changes in the Visum software. The conducted research showed that the planned transport network might result in induced traffic through a increase in accessibility (the central variant) with the assumption that an increase in mobility would be vented in the real face of the phenomenon of motility. The fact of opening new road sections of expressways will contribute to substantial changes in the directions of traffic flows only to a slight extent, and the only transformations concern regions with already developed fast car transport infrastructure whose functionality is limited due to the lack of its cohesion in the subsequent course or lack of a developed network of expressways and motorways.